A aplicação dos princípios da comunicação pública e sua relação com a cidadania nas instituições públicas de ensino superior de Goiás - Justino, Stephanie Silva (2019)
This research aimed to understand if the principles and characteristics of public communication are applied by communication professionals in public higher education institutions in the state of Goiás. The locus of analysis of the research were the communication sectors of the Federal Institute of Education, Science and Goian Technology (IF Goiano), Federal Institute of Education, Science and Technology of Goiás (IFG), State University of Goiás (UEG) and Federal University of Goiás (UFG). In order to analyze the application of these principles, the study contextualized the origin of higher education institutions in Brazil in order to understand the organizational culture of these institutions and the challenges that exist for the actions and communication practices in these spaces. Then, the bibliographical review of the concepts of citizenship and public communication was carried out and the relationship between higher education, the conquest of citizenship rights and the contribution of the public institution of higher education communication actions were strengthened in order to bring these institutions closer to the society and for the promotion of citizenship. Based on the principles of Public Administration established in the Constitution of theFederative Republic of Brazil of 1988 (CRFB), the pre-requisites and principles listed by Jorge Duarte (2011) and Zémor (2009) synthesized There are seven aspects of public communication that guided the analysis of the research: Public interest as a focus and priority; Information deciphered and widely disseminated; Transparency, oversight and accountability; Egalitarian dialogue; Ethics and responsibility; Encouraging participation and Shared management. To collect the research data, we used the methodological approach of triangulation. The triangulated data were collected through five different instruments and research techniques. The first was the documentary analysis of the specific and general communication policies of institution of higher education. The second was the application of a questionnaire with 27 questions sent by e-mail to 107 communication professionals. The third was the direct observation, carried out for 10 days in the communication sectors in the rectories of IF Goiano, IFG, UEG and UFG. In addition to the observation, in-depth interviews were conducted with the communication managers of the four institutions. Finally, we analyzed the content of the posts made during the days of observation in the institutional sites and in the official profile of the institutions in Instagram. The data collected in the research were analyzed in four different dimensions. The first dimension is related to the knowledge of the principles of public communication by professionals. The second refers to the motivation of professionals to apply these principles. The third analyzes the impediments found for the application of the principles. The fourth and last one verifies, in the professional performance, when the principles are or are not practiced. As a result of the research, it was found that most professionals know the concept of public communication, but not the principles and characteristics that are often mixed and confused with institutional communication. Regarding motivation, even those who do not know the principles, are interested in making actions and communication products and that dialogue with the community. Some professionals have shown lack of motivation due to the number of impediments they encounter in order to implement improvements, especially in relation to organizational culture, management vision, bureaucracy and lack of financial, human and material resources. Although not fully applied, the principles of public communication are observed in actions and practices of the communication sectors of the four institution of higher education in the state of Goiás.